NOTES ON THE FLORAL MORPHOLOGY AND ANATOMY OF TESSMANNIANTHUS CARINATUS (MELASTOMATACEAE) - Kriebel, Ricardo (Caldasia, 2014)
This work reports the second collection of Tessmannianthus carinatus Almeda, a species previously known only from the type. Two flowering trees were encountered at the type locality of Cerro Jefe, Panama. Species in this genus are very rare and the colors and posture of fresh floral parts have seldom been observed and described. The first known images of flowers at anthesis are here provided. In addition, observations on the posture and color of the stamens were made, including dissections of a flower preserved in spirit, and scanning electron micrographs of the unusual anther apices. Lastly, anatomical sections were conducted of these flowers which revealed the presence of styloids in the hypanthium, anthers and styles. These crystals had only been reported from the wood of one species in the genus and their presence suggests a relationship to the tribes Astronieae and Henrietteeae